Is agricultural labour feminizing in South and South East Asia: Analysis of demography and health services data on women and work - Oloo, Stephen; Galiè, Alessandra; Teufel, Nils (Frontiers Media, 2023)
'Feminisation of agriculture’ is generally utilized to indicate an expansion of women’s engagement in agricultural production, as labourers or decision-makers. Feminization of Agriculture is often reported as a global trend. While literature on feminization of agriculture (FoA) has seen a steady rise in the last decade, there is little consensus on defining feminization of agriculture and consistent approaches that provide comparative quantitative data on FoA are lacking. This compromises the ability to provide a comparative understanding of the extent of feminization across various regions. In this paper, we develop a methodological approach to assessing the extent of FoA and deploying it on DHS data from South and South-East Asia. Our data show that in Cambodia, India, Indonesia and Nepal the trend has been towards a Masculinization of Agriculture between 2005 and 2017, while no trend could be determined for the Philippines. We discuss the implications of our results while highlighting some of the limitations of our approach and suggesting possible next research steps.